Microcontroller based application of bio-sensing the critical parameters of the human lung - Babulal, Swathi; Binzaid, Shuza; Guo, Ruyan; Bhalla, Amar (Integrated ferroelectrics, 2016)
A comprehensive study of the thermal exchange of airflow during respiration was carried out and verified on human subject for non-invasive observation setup. The mechanism was parameterized into its electrical references and descriptions. Latter was found for critical parameters translated into electronic analogous signals. Important physical nodal points in the human breathing system are identified for temperature of exhale which is always between 41.1°C and 48.8°C and also it was found that humidity variations of inhale at 40 mg/l water contents having 100% RH which immediately reduced by 66% at exhale. This study was carried out by electromechanical setup of the system using sensors. Two types of custom processed sensors of NTC bead-type SiC and B 4 C as thermistors and GE EMD-4000 as humidity sensors that were modified at MeMDRL were used for such studies by carefully processing with bio-safe materials on these commercially available sensors; those were made suitable as bio-applicable sensors. The glass-like hardened non-hazardous Polyurethane μ-coating cured at constant temperature of 104°C for 18 hours were used. Special program for Arduino microcontroller system was created for the custom designed electronic hardware to control based on accurately processed data of sensor systems. Two sets of algorithms were computed to linearize all data forming at constant slope. By implementing HW/SW applications; the system can detect and measure the thermal energy and can convert into useful electrical power while breathing.